The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/hcre.12076
|View full text |Cite
|
Sign up to set email alerts
|

Story Perspective and Character Similarity as Drivers of Identification and Narrative Persuasion

Abstract: Identification with a character is an important mechanism of narrative persuasion. In 2 studies, the impact of character similarity on identification was pitted against that of story perspective. Participants read stories in which a lawyer (Study 1) and a general practitioner (GP; Study 2) had a conflict with another character. Perspective was manipulated by describing the events as experienced and narrated by the lawyer (GP) or their opponent. In Study 1 (N = 120), 60 participants were law students, in Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
1
10

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(120 citation statements)
references
References 47 publications
2
84
1
10
Order By: Relevance
“…This study also makes a significant contribution to research into narrative persuasion and the role of emotions and identification with characters as explanatory mechanisms (de Graaf, 2014;de Graaf et al, 2012;Hoeken & Fikkers, 2014;Hoeken et al, 2016;Hoeken & Sinkeldam, 2014;Igartua & Barrios, 2012;Igartua & Vega, 2016).…”
Section: Conclusion and Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…This study also makes a significant contribution to research into narrative persuasion and the role of emotions and identification with characters as explanatory mechanisms (de Graaf, 2014;de Graaf et al, 2012;Hoeken & Fikkers, 2014;Hoeken et al, 2016;Hoeken & Sinkeldam, 2014;Igartua & Barrios, 2012;Igartua & Vega, 2016).…”
Section: Conclusion and Discussionmentioning
confidence: 87%
“…Previous research has shown that the characteristics of characters condition reception processes (such as appraisal of the character, emotions and identification) (Hoeken & Sinkeldam, 2014), that identification plays an important role in emotional activation (the greater the identification, the greater the emotional impact) (Hoeken, Kolthoff, & Sanders, 2016), and that, in addition, it is an important mechanism in explaining the impact of narratives on attitudes (together with emotions) (de Graaf et al, 2012;Igartua & Vega, 2016).…”
Section: Similarity Identification With Characters and Persuasive Imentioning
confidence: 99%
See 3 more Smart Citations